Influence of fermentation with different lactic acid bacteria and in vitro digestion on the change of phenolic compounds in fermented kiwifruit pulps. (27th August 2021) - Chen, Xiao; Yuan, Minlan; Wang, Yuting; Zhou, Yan; Sun, Xiaohong
Abstract: The present study aimed to evaluate the effect of fermentation and gastrointestinal digestion of three kinds of fermented kiwifruit pulps with different Lactobacillus ( Lactobacillus plantarum, Lactobacillus acidophilus and Lactobacillus casei ). The changes in bioactive substances (total phenolic acid, total flavonoid, vitamin C and the viable count), antioxidant capacity (DPPH, ABTS, hydroxyl radical and superoxide anion radical scavenging activity) and phenolic profiles (protocatechuic acid, protocatechualdehyde, chlorogenic acid, caffeic acid and p ‐coumaric acid) were detected. The result showed, compared to non‐fermented kiwifruit pulp, fermentation with LP and LA had higher content of TPA, TF and VC, as well as antioxidant capacity. Fermentation with LP and the content of protocatechualdehyde, p ‐coumaric acid and chlorogenic acid were increased. However, after digestion, LP showed more effect in maintaining the content of antioxidants, antioxidant capacity and the viable count rather than LA . During digestion, the content of protocatechualdehyde and p ‐coumaric acid was increased in fermented samples compared with non‐fermented samples. Overall, compared with LA and LC, LP is more suitable for the fermentation of kiwifruit pulp. Abstract : The fermentation of kiwifruit had its influence on the content of antioxidant substance and antioxidant activity.